Geant4 simulation of the dual phase Time Projection Chamber TPC of argon to detect neutrinos - Huancco, IJ (2018)
The present work describes the simulation carried out in Geant4 of a Time Projection Chamber TPC of argon that uses not only a dual-phase technology (liquid and gas) but also PhotoMultiplier tubes PMT for the detection of scintillation caused by the interaction of charged particles with argon. Furthermore, the optoelectronic characteristics of the PMT are analyzed. This allows the study of particles production through the neutrino-nucleus interactions.